Is foreign direct investment losing clout in development - Axel Berger; Alexandros Ragoussis (Deutsches Institut für Entwicklungspolitik (DIE), 2022)
Over the last decade, only a single projection of foreign direct investment (FDI) flows by the United Nations influential "World Investment Report" has proposed a negative outlook in the medium term. Based partly on surveys of business executives, these forecasts reflect expectations of investment growth which, however, have repeatedly failed to materialise. In fact, FDI flows to developing countries have remained stagnant over the past decade. Such wishful thinking is nurtured by a long series of positive narratives and facts about foreign investment. FDI has been one of the pillars of international development efforts for over 70 years. Its promise has not been limited to critical finance, but extends to longer term competitiveness through access to better technology, managerial know-how and, above all, prosperity through more and better paid jobs in the formal sector. From the old prescriptions of the so-called Washington Consensus to the hopeful Addis Ababa Action Agenda, the dominant development narrative has therefore favoured a rather indiscriminate pursuit of investment volume. This brief calls for rethinking of narratives and policies that help to improve the impact of FDI, based on secular trends that challenge our expectations. Four such trends stand out: First, while other sources of finance for development have grown considerably over the last decades, foreign investment has not followed the trend. Second, the kind of investment that is associated with stronger gains and longer term commitment in host economies - greenfield FDI - has also been in consistent decline as a share of total investment, while mergers and acquisitions and project finance have gained in importance. Third, the top 100 multinational enterprises (MNEs), accounting for nearly a quarter of global FDI stock, rely less on employment today than they used to in order to grow their foreign presence. Job creation, knowledge transfer and spillovers are therefore less likely to materialise through the presence of mega-firms and their corresponding investment at scale. Fourth, the growth of Chinese outward FDI within a strategic expansionary political agenda stands to change rules and attitudes towards foreign investment moving forwards. We argue that, collectively, these trends invite a renewed conversation around the kind of foreign investment we want and expectations of this source of finance for development. These facts obscure neither the broad benefits of FDI to developing countries, nor the value proposition of FDI attraction. Rather, they raise questions about expectations, priorities and the alignment of investment policy with the realities experienced across developing countries. To that end, we propose four priorities that stand to make a difference in the current context. We call for policy-makers to: 1) Place additional emphasis on retention of investment and linkages with the domestic economy. 2) Try new approaches for FDI attraction that focus on improving domestic investment facilitation frameworks. 3) Be selective as to investment sources and activities in order to mitigate political risks and align inward investment better with sustainable development. 4) Add evidence to improve our understanding of investment and inform decision-making. Overall, it is critical to engage in a serious multi-stakeholder conversation around expectations, actors and solutions that respond to the investment reality of today.
Keywords: 330